An Analysis of Student’ Writing Difficulties in Online Learning During COVID-19 Pandemic At 4TH Semester in Muhammadiyah University of Bengkulu - Ririn Putri Ananda; Muhammad Rezy Astriyadi; Feny Martina (Teaching English and Language Learning English Journal, 2023)
Writing is a complex and essential skill that plays a significant role in communication, education, and professional endeavors. However, many students encounter various difficulties when engaging in writing tasks, especially in covid-19 pandemic. The aim of the research is to find out student’s writing difficulties in online learning during COVID-19 pandemic at 4TH semester in Muhammadiyah University of Bengkulu. The design of this research was descriptive method. The instrument of the research was questionnaire. The result showed that there are four factors that make fourth semester students have writing difficulties in online learning during pandemic Covid 19, namely : organization, content of the text, grammar and vocabulary mastery. The dominant factor of the students writing difficulties is vocabulary mastery. It implies that the students need to practice regularly and set aside dedicated time for writing practice. In addition, the students can seek support if they are still facing persistent challenges in writing, consider seeking additional support from lecturers, counselors, or professionals specializing in learning writing difficulties to help them in personalizing strategies and interventions tailored to the students' specific needs especially enhancing their knowledge about organization, content, grammar and add their vocabularies. Key words: Writing, Online Learning, Writing Difficulties